Innovative Employee Training and Development: Catalyzing the Green Economy Transition through Strategic HR Management - Nasution, Rizki Alfadillah; Panjaitan, Santi Rohdearni (International Journal of Economics Development Research (IJEDR), 2024)
This study investigates the impact of Innovative Employee Training and Development on the Green Economy Transition, with a focus on the mediating roles of Employee Competency Enhancement and Strategic HR Management. Using a quantitative approach and analyzing data from 61 employees at the North Sumatra Provincial Communication and Information Office, the research employs SmartPLS for data analysis. The findings reveal that Innovative Employee Training and Development significantly enhances Employee Competency, which in turn positively influences the Green Economy Transition. Additionally, Strategic HR Management mediates the relationship between training and the green transition, further demonstrating its critical role in integrating sustainability into organizational practices. The results emphasize the importance of investing in advanced training programs and strategic HR management to drive environmental sustainability and achieve organizational goals related to the green economy. These insights provide valuable implications for organizations aiming to foster a sustainable future through effective employee development and strategic HR practices.